FACTORS AFFECTING THE FAILURE OF CALF LINES OF DRILLING RIGS - Іващенко, Василь Трифонович; Лях, Михайло Михайлович; Журавльов, Дмитро Юрійович; Михайлів, Вадим Владислович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The paper analyses the main factors influencing the durability of a calf line. They are the nonsteady cyclic nature of changes in tensile stress and bending stress in rope wires, dynamic (oscillatory) character of the system operating mode: drilling stem - calf line - drilling rig. The process of wearing the material of rope wires is characterized: inside the rope and the external one. The quantitative estimation of the dynamic loading effect on the accumulation of fatigue factors is considered taking into account the fatigue curve of the rope. The analytical dependences of the influence of constructive and regime parameters of the work of the drilling line systems and their characteristics influencing the failure of the calf line are discussed.